2020
DOI: 10.1371/journal.pgen.1008433
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis receptor kinase STRUBBELIG regulates the response to cellulose deficiency

Abstract: Plant cells are encased in a semi-rigid cell wall of complex build. As a consequence, cell wall remodeling is essential for the control of growth and development as well as the regulation of abiotic and biotic stress responses. Plant cells actively sense physico-chemical changes in the cell wall and initiate corresponding cellular responses. However, the underlying cell wall monitoring mechanisms remain poorly understood. In Arabidopsis the atypical receptor kinase STRUBBELIG (SUB) mediates tissue morphogenesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 84 publications
(176 reference statements)
0
33
0
1
Order By: Relevance
“…This prevention also requires nitric oxide (NO) release, possibly generated by NITRATE REDUCTASE1 NITRATE REDUCTASE2 (NIA1 NIA2) [80]. Intriguingly, CWI impairment caused by cellulose biosynthesis inhibition induces the production of ROS, while responses like JA/SA/lignin production are NIA1 NIA2-dependent [61,94] ( Figure 1B). FER acts through a guanine nucleotide exchange factor-plant RHO-related GTPase (GEF-ROP/RAC) pathway to regulate ABA-based signaling while also being regulated in turn by ABA, hinting at the existence of regulatory feedback loops that may also affect turgor pressure levels in plant cells [95,96] ( Figure 1B).…”
Section: Receptor-mediated Cell Wall Integrity Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevention also requires nitric oxide (NO) release, possibly generated by NITRATE REDUCTASE1 NITRATE REDUCTASE2 (NIA1 NIA2) [80]. Intriguingly, CWI impairment caused by cellulose biosynthesis inhibition induces the production of ROS, while responses like JA/SA/lignin production are NIA1 NIA2-dependent [61,94] ( Figure 1B). FER acts through a guanine nucleotide exchange factor-plant RHO-related GTPase (GEF-ROP/RAC) pathway to regulate ABA-based signaling while also being regulated in turn by ABA, hinting at the existence of regulatory feedback loops that may also affect turgor pressure levels in plant cells [95,96] ( Figure 1B).…”
Section: Receptor-mediated Cell Wall Integrity Monitoringmentioning
confidence: 99%
“…With the binding specificity of FER and THE1 for RALF peptides apparently changing in a pH-dependent manner, RALFs interacting with more than one CrRLK, and FER regulating AHA2 activity, additional regulatory levels exist, which suggests that fine-tuning of the signaling activity and coordination between different CrRLKs may occur [79,86,97]. Signals from THE1 and FER are possibly relayed via NO-and/or ROS-based signaling cascades [73,80,94]. THE1 is required for JA/SA production in response to CWI impairment ( Figure 2C), while loss of FER actually leads to enhanced JA/SA production [73].…”
Section: How Do the Different Sensing Mechanisms Contribute To Cell Wmentioning
confidence: 99%
“…However, at present, to directly assay cell wall sensing in planta is still elusive. With this note of sobriety, a shortlist of Arabidopsis thaliana loci encoding receptorlike molecules previously implicated with CWI includes WALL ASSOCIATED KINASE 1 (WAK1) and its paralogs [12]; THESEUS1 (THE1), FERONIA (FER) and other Malectin-like receptor kinases [13]; BRASSINOSTEROID INSENSITIVE 1 (BRI1) and RECEPTOR-LIKE PROTEIN 44 (RLP44) [14,15]; MALE DISCOVERER INTERACTING LOCUS 2 (MIK2) [16]; STRUBBELIG (SUB) [17]; as well as FEI1 and FEI2 (see below). Together with FASCICLIN-LIKE ARABINOGALACTAN PROTEIN 4 (FLA4) also known as SALT OVERLY SENSITIVE 5 (SOS5), the two FEI loci form the core components of a putative signaling module apparently involved in CWI maintenance throughout the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Present evidence indicates that SUB fulfills its role in these developmental processes in a complex with the transmembrane protein QUIRKY (QKY) (Fulton et al, 2009;Song et al, 2019;Trehin et al, 2013;Vaddepalli et al, 2014). Recent work has revealed that SUB also participates in the isoxaben-induced CWD response in young seedlings (Chaudhary et al, 2020). Interestingly, QKY was found to play only a minor role in this process.…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, QKY was found to play only a minor role in this process. Moreover, SUB, THE1, and MIK2 appear to function in different CBI-induced CWD pathways (Chaudhary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%